Identifying the Barriers and Opportunities in the Provision and Use of Weather and Climate Information for Flood Risk Preparedness: The Case of Katakwi District, Uganda - Mitheu, Faith; Petty, Celia; Tarnavsky, Elena; Stephens, Elisabeth; Ciampi, Luisa; Butsatsa, Jonah; Cornforth, Rosalind (Frontiers in Climate, 2022)
The provision of weather and climate information (WCI) can help the most at-risk communities cope and adapt to the impacts of extreme events. While significant progress has been made in ensuring improved availability of WCI, there remain obstacles that hinder the accessibility and use of this information for adaptation planning. Attention has now focused on the ‘usability gap’ to ensure useful and usable WCI is used to inform practice. Less attention has however been directed on barriers to active production and use of WCI. In this study, we combine two frameworks to present a more coordinated institutional response that would be required to ensure a better flow of information from the information providers to the users and vice versa. Focusing on Uganda, a bottom-up approach is used to identify the barriers and opportunities in the production/provision and use of WCI for flood risk preparedness. First, a use-case is developed for Katakwi District where smallholder farming communities have recorded their coping practices and barriers to the use of WCI in practice. Second, online interviews with practitioners from disaster management institutions are used to identify the barriers to the production and provision of WCI to the local farming communities. Findings show that for providers, barriers such as accessibility and completeness of data hinder the production of useful WCI. In situations where useful information is available, technical language used in the format and timeliness in dissemination hinder usability by local farmers. Useful and usable WCI is not used in practice due to the social-economic capacity of the communities e.g., lack of access to improved seeds. Our study highlights the importance of a more coordinated response that would ensure a shift of focus from only the users to a more inclusive approach where even the data and information needs of the providers are considered to improve disaster risk management. While such considerations alone might not be enough to ensure effective use of WCI at the local level, we argue that understanding these data and information gaps across the provider-user landscapes can help in shaping disaster management activities at both the national and local level.